Historical notes on graft and corruption in the Philippines - Endriga, Jose N. (1979)
The phenomenon of graft and corruption in the present Philippine bureaucracy could be traced to the Philippine colonial experience, especially during the Spanish period, but certain features in the culture of pre-conquest Philippines could be described as amenable to corrupt behavior. It was during the American period that public service was very much improved because (1) adequate compensation was given to. those in the civil service; and (2) the civil
service law was effective in punishing guilty officials. The climate of rectitude was maintained throughout the Commonwealth period.
Keywords: Political corruption; Politics and public administration; Public administration -- Moral and ethical aspects